The Lipid Profiles in Different Characteristics of Women with PCOS and the Interaction Between Dyslipidemia and Metabolic Disorder States: A Retrospective Study in Chinese Population - Guo, Fei; Gong, Zhentao; Fernando, Taniya; Zhang, Lingshan; Zhu, Xiaoyong; Shi, Yingli (Frontiers in Endocrinology, 2022)
Abstract Purpose: To exhibit the lipid profiles in PCOS women with different characteristics and to access correlations between alternation of key lipid parameters and characteristics of PCOS. Design: A retrospective study. Participants: A total of 700 PCOS women were included. Methods: Retrospective study on 700 women (age 24.6 ± 4.7 years), diagnosed with PCOS in the outpatient department of Obstetrics and Gynecology Hospital of Fudan University according to Rotterdam criteria. Anthropometric features, hormone levels, lipid levels, and metabolic parameters were measured and compared between PCOS patients with different characteristics. Results: There was a high prevalence of dyslipidemia among Chinese PCOS patients (41.3%), and the most common pattern was low HDL. Patients with clinical hyperandrogenism presented with significantly decreased HDL and Apo-A levels. The levels of TG, LDL, Apo-B, TG/HDL, and Apo-B/Apo-A were significantly increased in the insulin resistance subgroup. The levels of TC and TG were significantly increased in the dysglycemia and T2DM women. And in general, the levels of TG, and Apo-B had an increasing trend with BMI. Moreover, AI, TG/HDL, and Apo-B/Apo-A ratios were associated with some characteristics of PCOS, such as insulin resistance, and obesity. Conclusion: The PCOS women with different characteristics presented with different lipid profiles, and there is a complex correlation between lipid metabolism and PCOS characteristics, which may explain the increased risk of long-term cardiovascular disease. Regular screening of blood lipids is essential for PCOS women. Identification of optimal subgroups in PCOS patients that need lipid-lowering treatment and therapeutic effectiveness is worth exploring.